Elevated preoperative C‐reactive protein is associated with renal functional decline and non‐cancer mortality in surgically treated renal cell carcinoma: analysis from the INternational Marker Consortium for Renal Cancer (INMARC). (19th November 2020) - Cotta, Brittney H.; Meagher, Margaret F.; Patil, Dattatraya; Saito, Kazutaka; Patel, Sunil H.; Patel, Devin N.; Miller, Nathan; Dutt, Raksha; Keiner, Cathrine; Bradshaw, Aaron W.; Wan, Fang; Eldefrawy, Ahmed; et al.
Abstract : Objective: To investigate association of preoperative C‐reactive protein (CRP) and non‐cancer mortality (NCM) in a cohort of patients undergoing surgery for localised renal cell carcinoma (RCC). Patients and Methods: Retrospective multicentre analysis of patients surgically treated for clinical Stage 1–2 RCC from 2006 to 2017, excluding all cases of cancer‐specific mortality. Descriptive analyses were obtained between the pre‐treatment normal‐CRP (≤5 mg/L) and elevated‐CRP (>5 mg/L) groups. The primary outcome was NCM. The secondary outcomes included progression to de novo chronic kidney disease Stages 3–4 (estimated glomerular filtration rate [eGFR] of <60, <45, and <30 mL/min/1.73 m 2 ). Multivariable analyses (MVA) were performed to assess for risk factors associated with functional decline and NCM, and Kaplan–Meier analysis was used to obtain survival estimates for outcomes. Results: A total of 1987 patients who underwent radical or partial nephrectomy were analysed (normal‐CRP group, n = 963; elevated‐CRP group, n = 1024). Groups were similar in age (59 vs 60 years, P = 0.079). An elevated CRP was more frequent in males (36.8% vs 27.8%, P < 0.001), African‐Americans (22.6% vs 2.9%, P < 0.001), and in those with a higher median body mass index (30 vs 25 kg/m 2, P < 0.001) and larger median tumour size (4.5 vs 3.3 cm, P < 0.001). On MVA, an elevated CRP was independently associated with development of de novo eGFR of <60 mL/min/1.73 m 2 (hazard ratio [HR] 1.32, P = 0.015), <45 mL/min/1.73 m 2 (HR 1.41, P = 0.023) and <30 mL/min/1.73 m 2 (odds ratio 2.23, P < 0.001). The MVA for factors associated with NCM demonstrated increasing age (HR 1.06, P < 0.001), preoperative elevated CRP (HR 2.18, P < 0.001) and an eGFR of <45 mL/min/1.73 m 2 (HR 1.16; P = 0.021) as independent risk factors. Kaplan–Meier analysis revealed significantly higher 5‐year NCM in the elevated‐CRP group vs the normal‐CRP group (98% vs 80%, P < 0.001). Conclusions: Pre‐treatment elevated CRP was independently associated with both progressive renal functional decline and NCM in patients undergoing surgery for Stage 1–2 RCC. Patients with elevated CRP and Stage 1 and 2 RCC may be considered as having indication for nephron‐sparing strategies, which may be prioritised if oncologically appropriate.